The Relationship between Freedom and Justice in the Political Thought of John Rawls - Ajlouni, Heba Ahmad Mohammad (Dirasat: Human and Social Sciences, 2023)
Objectives: This study aimed to clarify the relationship between the values ​​of freedom and justice, by analyzing the philosophical political thought of John Rawls. Freedom and justice together constituted the main pillar in Rawls political thought. Methods: The study used the descriptive-analytical approach, within the framework of constructivism to analyze Rawls theory of justice as fairness. That helped to reach consistent results linking freedom and justice in a mandatory way. Also, the study used the inductive method which helped to reach new logical intellectual results. Results: The study revealed a strong link between freedom and justice, particularly by analyzing Rawls' theory of justice as fairness. Rawls emphasized that freedom is integral to a just society and skillfully balanced the relationship between the two. He demonstrated that political systems, guided by principles of justice and responsible, regulated freedom, can create a potent synergy. Rawls' strategic alignment of politics, justice, and freedom not only preserved a liberal political system but also enhanced its effectiveness with a renewed moral foundation. Conclusions: Based on the study's findings, the key recommendation is to ensure justice prevails within all state institutions while upholding freedom as a crucial component. Freedom is vital for human dignity and aligns with human nature. Additionally, it is advised to incorporate John Rawls' philosophy as a moral and political reference.